Fluoroquinolones biosorption onto microbial biomass: activated sludge and aerobic granular sludge. (May 2016) - Ferreira, Vanessa R.A.; Amorim, Catarina L.; Cravo, Sara M.; Tiritan, Maria E.; Castro, Paula M.L.; Afonso, Carlos M.M.
Abstract: Fluoroquinolones (FQs) have been reported in trace amounts in different environmental matrices. The biosorption of three most prescribed FQs, ofloxacin (OFL), norfloxacin (NOR) and ciprofloxacin (CPF) by activated sludge (AS) and aerobic granular sludge (AGS) was investigated. Biosorption assays were conducted with FQs concentrations within the range of 100–700 ng mL −1, to mimic environmental conditions. At neutral pH and at the end of 48 h, AS showed higher biosorption capacity than AGS. For AS, a maximum biosorption of 1.50 ± 0.03, 3.24 ± 0.05 and 3.39 ± 0.06 mg gTSS −1 was observed for OFL, NOR and CPF respectively, whereas for AGS the maximum amount of FQs biosorbed was 1.18 ± 0.03, 2.73 ± 0.02 and 2.94 ± 0.03 mg gTSS −1 . Langmuir isotherm was more applicable for describing FQs biosorption equilibrium by AS while for AGS, the Freundlich isotherm was more adequate. Given the AGS technology innovative character, the effect of change of pH on the biosorbed FQs was evaluated. FQs could be desorbed from AGS at pH 3, pH 8 and pH 9 but at pH 4 the biosorption process was promoted. This study allows a better understanding of the FQs biosorption processes. Moreover, the data from biosorption/desorption from AGS may be useful for management and operation of AGS bioreactors. Highlights: Biosorption of OFL, NOR and CPF to AS and AGS was studied. Biosorption extent of OFL, NOR and CPF onto AS was higher than onto AGS. OFL was the less biosorbed FQ, both onto AS and AGS. The fate of the previously biosorbed FQs on AGS at different pH was evaluated. The pH affected the biosorption capacity of AGS.